2014
DOI: 10.2179/13-045
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Seed Treatments and Fertilizer on Growth ofPenstemon tubaeflorus

Abstract: Penstemon tubaeflorus is a North American prairie forb of conservation concern.Protocols for seed germination and transplant production involving fertilization are needed for conservation purposes. Our objectives were to compare techniques for breaking seed dormancy and increasing germination, and to investigate fertilizer on growth of Penstemon tubaeflorus. Seed treatments were hickory smoke seasoning solution (1:10, 1:100, 1:500, and 1:1,000), light vs. dark, prairie plant ash solution (2, 4, 8, and 16 g/L),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 17 publications
1
2
0
Order By: Relevance
“…There was no advantage to using liquid fertilizer every week versus every other week. Our results showing increased seedling size with slow‐release fertilizer agree with those for Penstemon tubaeflorus (Annis et al 2014) and for Schizachyrium sanguineum (de Oliveira et al 2022), although liquid fertilizer also increased seedling size for S. regia , but did not for P. tubaeflorus (Annis et al 2014). While the number of leaves on plants before planting differed between planting seasons it was not a consistent effect.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…There was no advantage to using liquid fertilizer every week versus every other week. Our results showing increased seedling size with slow‐release fertilizer agree with those for Penstemon tubaeflorus (Annis et al 2014) and for Schizachyrium sanguineum (de Oliveira et al 2022), although liquid fertilizer also increased seedling size for S. regia , but did not for P. tubaeflorus (Annis et al 2014). While the number of leaves on plants before planting differed between planting seasons it was not a consistent effect.…”
Section: Discussionsupporting
confidence: 88%
“…In the case of seedlings of Penstemon tubaeflorus (white wand beardtongue) grown in growth chambers, Annis et al (2014) reported increased shoot mass, number of leaves, and root length in seedlings with slow‐release fertilizer and no increased growth with liquid fertilizer compared to control with no fertilizer. For Schizachyrium sanguineum (crimson bluestem), controlled release fertilizer resulted in increased growth of seedlings in a plant nursery (de Oliveira et al 2022).…”
Section: Introductionmentioning
confidence: 99%
“…The cold treatment of A. thaliana seeds relates in a similar manner to that of seed sterilization, as both of these tasks allow for a higher seed survival rate, in addition to an increase in germination rates (Annis et al 2014). Ultimately, this procedure is quite simple and only requires microcentrifuge tubes and sterilized water, which can be created by boiling water and allowing it to cool to room temperature.…”
Section: Methodsmentioning
confidence: 99%